Study of Double Charm B Decays with the LHCb Experiment at CERN and Track Reconstruction for the LHCb Upgrade - Quagliani, Renato (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book discusses the study of double charm B decays and the first observation of B0-‰D0D0Kst0 decay using Run I data from the LHCb experiment. It also describes in detail the upgrade for the Run III of the LHCb tracking system and the trigger and tracking strategy for the LHCb upgrade, as well as the development and performance studies of a novel standalone tracking algorithm for the scintillating fibre tracker that will be used for the LHCb upgrade. This algorithm alone allows the LHCb upgrade physics program to achieve incredibly high sensitivity to decays containing long-lived particles as final states as well as to boost the physics capabilities for the reconstruction of low momentum particles.